Intāj al-Kharāʼiṭ wa-Ṭibāʻatuhā bi-Salṭanat ʻUmān - ʻAbd al-ʻĀl, Sayyid Ramaḍān Sayyid (al-Muʼtamar al-Duwalī al-Khāmis bi-Mālīziyā: Ḥarakat al-Ṭibāʻah al-ʻUmānīyah wa-Atharuhā fī al-Tawāṣul al-Ḥaḍārī, 2018)
The importance of this study lies in its uncovering of an important aspect of the history of printing in the Sultanate of Oman — namely the printing of maps — despite the scarcity of relevant information, an aspect of considerable importance for study given the value of maps themselves. On this basis the study traces the state of map production and printing in the Sultanate of Oman, treating the emergence of map printing and its development: maps were produced by traditional methods and then developed under the growth of digital technology and the successful use of computers in drawing, which forms an important part of geographic information systems. This stage was followed by map printing, which has witnessed substantial development in digital form. It may be noted that map production must follow the rules of cartography, which is among the important scholarly methods in this field.
MHF-PRINT2018-011
Keywords: Cartography; Map printing; Oman; Geographic information systems; Digital printing; History of printing